Avaliação da língua portuguesa para o aluno surdo: experiências em escolas públicas municipais de Pernambuco - Silva, Soraya Gonçalves Celestino da (2015)
This paper discusses the evaluation of the Portuguese Language for the Deaf student experiences in public schools in Pernambuco. We know that deaf education underwent a major evolutionary process to get to today, we see a breakthrough in the legislation, the contribution that ensures the presence of the interpreter in the classroom and recognition of Brazilian Sign Language (LIBRAS) as a first language (L1). Regarding the evaluation process the law guarantees them a differentiated assessment, and the teacher concerned to develop strategies to meet the specificity of these students. In this sense, we chose as a general objective to analyze the concepts and strategies used by teachers of the municipal public education system of Olinda and Paulista for the evaluation of deaf students. In this direction, our research is theoretical basis some scholars who talk about the assessment, such as Brazil ( 1996, 1997 , 2003, 2005 , 2006) ; Both ( 2012) ; Demo ( 2010) ; Hoffmann (1994, 2009 , 2013 , 2014) ; Luckesi ( 1992, 1996 ); Perrenoud (1999 ); and while those who defend the Portuguese as L2, support us in Brochado (2003) and Krashen (1995); Freire (1998 ); Quadros (1997 , 2006 , 2011) and Skliar (1997 ) ; and those who advocate the evaluation of L2 : Bolsanello and Ross (2005); Russell & Airasian (2014) ; Thomas and Klein (2009 ) , among others. The methodology elected a grounded study in the interpretative qualitative descriptive character, had as data collection instruments semi-structured interviews with regular classroom teachers and textual production of deaf students and listeners. In analyzing the data, we analyzed the content from the perspective of Bardin (2011). The study subjects were three teachers of Portuguese Language, distributed in three regular classes from the 5th year of elementary school, one in Olinda and two in Paulista. In addition, we had three deaf students, aged 12-17 years and three hearing students. The results of the survey respondents indicated that most teachers, despite their claim of using adaptations in the activities of deaf students, as strategies, they experience difficulties in evaluating an inclusive class and define themselves as being unprepared. The analysis of the textual productions of deaf students and listeners indicate that the mostly concepts and evaluation strategies used in inclusive room are guided by the conception of the teaching of Portuguese as L1 and its type is still summative, as the strategies for application the evaluation of deaf students are restricted to the Educational Service Specialized room (ESA).